2005
DOI: 10.1109/temc.2004.842205
|View full text |Cite
|
Sign up to set email alerts
|

Convergence Acceleration and Accuracy Improvement in Power Bus Impedance Calculation With a Fast Algorithm Using Cavity Modes

Abstract: Abstract-Based on the cavity-mode model, we have developed a fast algorithm for calculating power bus impedance in multilayer printed circuit boards. The fast algorithm is based on a closed-form expression for the impedance matrix of a rectangular power bus structure; this expression was obtained by reducing the original double infinite series into a single infinite series under an approximation. The convergence of the single series is further accelerated analytically. The accelerated single summation enables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 13 publications
0
41
0
Order By: Relevance
“…Another popular method employs a cavity model [28]- [30]. Analytical expressions are readily available for simple geometries, and fast algorithms have been developed [31], [32]. Combined with the segmentation technique [33], [34], the cavity model can be used to model arbitrarily-shaped parallel-plane cavities.…”
Section: Modeling Noise Coupling In Multilayer High-speed Pcbsmentioning
confidence: 99%
“…Another popular method employs a cavity model [28]- [30]. Analytical expressions are readily available for simple geometries, and fast algorithms have been developed [31], [32]. Combined with the segmentation technique [33], [34], the cavity model can be used to model arbitrarily-shaped parallel-plane cavities.…”
Section: Modeling Noise Coupling In Multilayer High-speed Pcbsmentioning
confidence: 99%
“…(4) is used for calculating the self-input impedance (Z ii ), it was found that for a small port dimension the convergence of the single series is still poor and thousands of terms must be computed to obtain good accuracy. We have developed a fast algorithm (11) in which the convergence of the single series was in further accelerated analytically. With the fast algorithm, using just a few terms has been sufficient to achieve good accuracy.…”
Section: A Rectangular Power Busmentioning
confidence: 99%
“…Based on the cavitymode model, we have developed a fast algorithm for efficiently and accurately calculating the impedance of a rectangular power bus structure (9) (11) . The fast algorithm is based on a closed-form expression for the impedance Z-matrix of a rectangular power bus structure; this expression was obtained by reducing the original double infinite series into a single infinite series under an approximation.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of the TLM-based circuit model for PCB power distribution is seen, when the PCB model can be included in designing and simulating integrated circuits. Cavity resonator method is an analytical modeling technique to characterize the impedance matrix at port locations on a rectangular parallel-plane pair structure [9,10]. For arbitrary shaped parallel-plane structure, an integral-equation equivalent circuit method is proposed [11].…”
Section: Introductionmentioning
confidence: 99%